Catalytic Activity of Ferrates (NiFe2O4, ZnFe2O4 and CoFe2O4) on the Thermal Decomposition of Ammonium Perchlorate. Issue 3 (10th September 2019) - Zhang, Ming; Zhao, Fengqi; Yang, Yanjing; An, Ting; Qu, Wengang; Li, Hui; Zhang, Jiankan; Li, Na
Abstract: Three kinds of ferrates (NiFe2 O4, ZnFe2 O4 and CoFe2 O4 ) were prepared via the facile solvothermal method and characterized using SEM, TEM, XRD, XPS, FT‐IR and BET instruments. The NiFe2 O4, CoFe2 O4 and ZnFe2 O4 particles possess hollow structure with average particle size of 70, 220 and 360 nm, respectively. The catalytic performance of the ferrates for AP thermal decomposition were studied using DSC and TG‐DTG methods, and the decomposition mechanism of AP were suggested. The catalytic effects of different ferrates for AP thermal decomposition were significantly different. The CoFe2 O4 has the best catalytic activity, and the high thermal decomposition peak temperature ( T HDP ) and apparent activation energy ( E a ) of AP were decreased by 108.99 °C and 37.38 kJ mol −1 in the presence of CoFe2 O4 sample. Adding ferrates has no obvious influence on the gas‐phase decomposition products of AP, but has a great influence on the energy barrier of high temperature decomposition of AP. The excellent catalytic activity of CoFe2 O4 is mainly attributed to the synergistic interaction between Fe and Co, which is conducive to the thermal decomposition of AP. Abstract :